Perhitungan Anggaran Penjualan, Produksi, dan Beban Operasional Sebagai Dasar Penyusunan Anggaran Laba Rugi pada Shinshin Cireng Premium Cabang Cililin - Salsa Meysa Kandela; Jouzar Farouq Ishak (Indonesian Accounting Literacy Journal, 2026)
The research subject has not yet implemented a structured operational plan, resulting in decision-making that heavily relies on owner's subjectivity and leading to inventory shortages in several product variants. The study focuses on preparing an operational budget for the period of July 2026 to March 2027, aiming of sales targets, cost projections, and profit forecasts to support sustainability and growth business. This study employs a quantitative method with a descriptive approach. The research processes numerical data obtained through interviews and documentation, generating both subject and documentary data, thereby producing numerical outputs. The results indicate that, based on the Forecast Error Standard, the quadratic trend method is more appropriate for utilization than least squares method. Theoretically, this study contributes to the operational budgeting literature by demonstrating the application of forecasting-based budgeting in supporting more systematic planning and decision-making for micro and small enterprises. However, the study is limited to a single business entity, a relatively short planning period, and the use of historical internal data, which may limit the generalizability of the findings to other business contexts.